Traditional Rubber Jumping Game as a Play-Based Intervention to Improve Fine and Gross Motor Development in Early Childhood: Evidence from Two Classroom Action Research Cycles - Rizki Nurhasanah; Ida Windi Wahyuni; Zulkifli Zulkifli (IGI Active Living and Health Insight, 2026)
Purpose of the study: This study aimed to investigate the effectiveness of the rubber jumping game (permainan lompat karet), a traditional Indonesian game, in enhancing both fine and gross motor skills among Group B children (aged 5–6 years) at RA Asiah Pekanbaru, Riau Province, Indonesia. Materials and methods: A classroom action research (CAR) design was employed across two cycles, involving 10 participants (6 males, 4 females). Data were collected through direct observation using structured observation sheets with a four-point developmental rating scale (BB, MB, BSH, BSB). Quantitative descriptive and qualitative analyses were applied to evaluate children’s motor development progression across pre-cycle, Cycle I, and Cycle II phases. Results: Pre-intervention assessment revealed critically low mean scores for fine motor skills (6.00%) and gross motor skills (6.10%). Following Cycle I, fine motor scores increased to 12.00% and gross motor scores to 9.00%. After Cycle II, substantial improvements were observed with fine motor scores reaching 20.60% and gross motor scores reaching 18.40%. Classical learning completeness achieved 80%, categorized as “very high” based on established success criteria. By Cycle II, 70% of children attained “Developing Very Well” (BSB) status for both motor domains. Conclusions: The rubber jumping game demonstrated significant efficacy in enhancing both fine and gross motor skills in early childhood settings. The integration of traditional games into the early childhood education curriculum offers a culturally relevant, cost-effective, and enjoyable pedagogical strategy for holistic motor development.